Methamphetamine self-administration causes neuronal dysfunction in rat medial prefrontal cortex in a sex-specific and withdrawal time-dependent manner - Chen, Lihua; Kreko-Pierce, Tabita; Cassoday, Stefanie L.; Al-Harthi, Lena; Hu, Xiu-Ti (Frontiers in Pharmacology, 2025)
Methamphetamine (Meth) is one of the most widely used illicit drugs worldwide, exerting potent psychostimulant effects that fuels its highly addictive nature. Chronic Meth use is associated with severe cognitive impairments, particularly in executive functions, decision-making, and working memory, which persist long even after cessation of Meth use. These cognitive deficits are associated with dysfunction of glutamatergic pyramidal neurons in the medial prefrontal cortex (mPFC), which regulates addiction and cognition. Both human and animal studies highlight Meth-induced mPFC dysfunction that contributes to compulsive behaviors and relapse. Emerging evidence also highlights significant sex differences in Meth use disorder (MUD). Previous studies suggest that Meth-induced behavioral and neuronal dysfunctions are different between males and females, but the cellular and molecular mechanism are not fully understood. Using behavioral and electrophysiological approaches (whole-cell patching), this study determined certain sex differences in neuronal dysfunction in the mPFC of rats that self-administered Meth (Meth-SA) followed by a short (2–5 d) or long-term (≥30 d) withdrawal. We found that both male and female rats self-administered methamphetamine in a similar pattern; however, the resulting hypoactivity, hyperactivity, and calcium dysregulation in mPFC neurons differed between the sexes. Such sex-specific neuronal dysfunction was associated with, and depended on, short or long-term withdrawal, respectively. By understanding these sex-specific behavioral/neuronal differences following different Meth withdrawal period, our novel findings demonstrate the role of sex as a biological variable in Meth-use and relapse, and reveal the effects of drug-using environment on mPFC neuronal dysfunction during withdrawal, providing insights for gender-specific treatment strategies.